Urban Nightscapes and Night Politics - (:unkn) unknown (My University, 2016)
The « urban night » still appears as an academic frontier, especially in African studies. This contrasts sharply with the growing social, economic, political investments of nighttime in metropolis worldwide. The ambition of this introductory paper is thus to outline several issues arising from the study of the urban night, relying mainly on West African examples. Stressing the need to engage the night through a dialectical relationship with the diurnal time – and according to the heuristic tension that emerges from it – the text displays some aspects of contradictory debates of “nocturnity”. Incidentally, the concept of “nightscape” is considered critically through the lens of urban situations in West Africa.
Keywords: African Research